The impact of Bioversity International’s African leafy vegetables programme in Kenya - Gotor, Elisabetta; Irungu, C. (2010)
An effort by Bioversity and several partners in Kenya increased production, consumption and marketing of a wide range of African leafy vegetables (ALVs) and improved household welfare. Between 1996 and 2004, Bioversity International worked with partners in Kenya to revive the interest of researchers and ordinary people in these valuable foods. An impact assessment study showed that nearly two-thirds of households growing ALVs increased their income from ALVs, while nearly half had increased their consumption of ALVs. Bioversity was ranked as the most influential partner in promoting production and use of ALVs and in raising awareness of the value of ALVs.